WS2 pseudocapacitance interface material and preparation method and application thereof

The WS2 pseudocapacitor interface material prepared by hydrothermal reaction of sodium tungstate and thiourea combined with CTAB surfactant solves the problem of insufficient conductivity of carbon-based electrodes, and realizes an electrochemical method for efficient removal of heavy metal ions, significantly improving removal rate and stability reduce the risk of pollution.

CN119118202AActive Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411262517.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The prior art has problems in the treatment of heavy metal contaminated water with low removal efficiency, high cost, high pollution risk and poor material stability, especially the lack of conductivity and selectivity of carbon-based electrodes, which limits the application of electrochemical methods.

Method used

Sodium tungstate, thiourea and hydroxylamine hydrochloride were used to prepare WS2 pseudocapacitor interface material through hydrothermal reaction, and CTAB surfactant was added to improve the material morphology and dispersed particle size and improve its capacitance adsorption performance on heavy metal ions.

Benefits of technology

It has achieved efficient removal rate (more than 90%) of heavy metal ions such as Cr3+, Cd2+, Pb2+, Ni2+, Co2+, Cu2+, etc., and has reduced production costs and environmental pollution risks, and improved circulation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118202A_ABST
    Figure CN119118202A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials and heavy metal wastewater treatment, and discloses a WS2 pseudocapacitance interface material and a preparation method and application thereof. The preparation method comprises the following steps: uniformly dispersing sodium tungstate, thiourea, hydroxylamine hydrochloride and a surfactant in deionized water to obtain a mixed solution; and heating the mixed solution to 160-200 DEG C for hydrothermal reaction, and separating, washing and drying the reaction product to obtain the WS2 pseudocapacitance interface material. The preparation method disclosed by the invention is simple, mild in reaction condition and low in cost. The obtained WS2 pseudocapacitance interface material can be applied to capacitive adsorption and removal of heavy metal ions, and the removal efficiency of the WS2 pseudocapacitance interface material to the heavy metal ions such as Cr < 3 + >, Cd < 2 + >, Pb < 2 + >, Ni < 2 + >, Co < 2 + > and Cu < 2 + > can reach 90% or above. Compared with a conventional method, the method has the advantages of high energy efficiency, environmental friendliness, no pollution and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials and heavy metal wastewater treatment, and specifically relates to a WS2 pseudocapacitor interface material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry and the surge in industrial manufacturing enterprises, the problem of heavy metal industrial wastewater discharge has become increasingly prominent, seriously polluting water resources and posing a direct threat to public health. Copper, lead, zinc, cadmium, mercury, chromium, etc. are the most common and toxic heavy metal pollutants in wastewater. They have been listed as chemical pollutants of public concern by the World Health Organization. They can exist stably in the water environment and are not easily degraded naturally. Heavy metal pollutants enter the ecological water system and accumulate and amplify through the food chain, causing acute or chronic toxic effects on aquatic organisms and humans, and even death in the most dangerous cases. Therefore, efficient removal of heavy metal elements in wastewater is of great significance to the sustainable and healthy development of the heavy metal industry and environmental protection.

[0003] In recent years, domestic and foreign researchers have explored and optimized a variety of heavy metal ion removal methods, including adsorption, chemical precipitation, ion exchange and membrane separation technology, for the removal of various heavy metal pollutants. Although the above methods have shown certain heavy metal removal efficiency, their respective limitations cannot be ignored. The chemical precipitation method achieves the removal of heavy metals by forming insoluble precipitates, but the large amount of sludge produced in the process is prone to secondary environmental pollution; the ion exchange method uses exchange agents to capture heavy metals, but the oxidation sensitivity of the exchange agents limits their stability and life, and the frequent regeneration requirements significantly increase the operating cost and running cost; the membrane separation method is based on the separation characteristics of membrane materials and can effectively intercept heavy metal ions in water bodies. However, the membrane is easily blocked by pollutants or other impurities in the wastewater, resulting in decreased membrane performance and shortened service life, which in turn affects the effluent water quality; the adsorption method uses the high specific surface area or special functional groups of the material to adsorb heavy metals, but the difficulty of recycling and regeneration of the adsorbent and the limited efficiency limit its widespread promotion in practical applications. Therefore, the development of a technology that can efficiently, environmentally friendly, low-cost and selectively remove heavy metal ions from water is of great significance to the sustainable development of the environment.

[0004] Capacitive deionization technology is a new type of electrochemical water treatment technology that is environmentally friendly, pollution-free, low in energy consumption, and has great development potential. It has attracted more and more attention from researchers in recent years. The electrochemical method uses the redox reaction on the electrode surface to reduce heavy metal ions in water to a more stable and less toxic form, or directly reduce metal ions to metal elements on the electrode surface to achieve efficient removal of metal ions in the aqueous phase. Therefore, electrochemical methods are a more effective way to remove ions in the solution. The principle of capacitive deionization technology is similar to the mechanism of double-layer capacitance. By applying a certain voltage between the two electrodes to establish an electric field, the anions and cations in the solution move to the corresponding electrodes under the action of the electric field force, and finally adsorb on the surface of the electrode or precipitate on the surface of the electrode, thereby reducing the ion concentration in the solution. When the ions on the electrode surface reach saturation, the two electrodes are connected in reverse, and the ions adsorbed on the electrodes are released into the solution due to the loss of the electric field, so that the ions in the solution are enriched again and the electrodes are regenerated. The electrode is an important component of the capacitive deionization system and is the key to determining the effect of capacitive deionization. Commonly used electrodes are carbon-based electrodes. Carbon-based electrode materials, such as activated carbon, have rich pore structures and good adsorption properties. They mainly capture charged ions through the Coulomb force at the double-layer interface. However, most carbon-based materials have reached a development bottleneck due to their weak conductivity, weak capacitive adsorption capacity, and low selectivity. The development of new electrode materials has become a development need.

[0005] WS2 has a typical layered structure similar to graphite. The structure of WS2 is a sandwich-like layered structure, in which the inner layer (SWS) is strongly covalently bonded, and the interlayer is weaker van der Waals force, and the layers are easily peeled off. With WS2 as the main material, through insertion reaction, guest atoms or molecules can be inserted between the main layers to form intercalation compounds. Since the layers of WS2 layered compounds are bound by weak van der Waals forces, it is possible to introduce foreign ions, atoms or molecules between the layers. The above characteristics have made WS2 widely studied in electrode materials. For example, patent CN108039289 A discloses a method for preparing WS2 nanomaterials with a macroporous mesh structure, using tungsten hexachloride (WCl6) and thioacetamide (CH3CSNH2) as raw materials, and adding carbon cloth for hydrothermal reaction to obtain WS2-carbon paper nanomaterials. It can be applied to photocatalysis, wastewater treatment, lithium ion batteries, biosensors and other fields. Patent CN 105664836 A discloses a method for preparing WS2 / WO3 hollow microspheres, using tungsten chloride and thioacetamide as raw materials, preparing WS2 / WO3 precursors by hydrothermal method, and then obtaining the product WS2 / WO3 hollow microspheres by high temperature heat treatment. The prepared product can quickly and thoroughly adsorb dyes such as rhodamine B, methyl orange, and methylene blue, and can be used for printing and dyeing wastewater treatment. However, the sulfur active sites of WS2 obtained by the above preparation method are difficult to control, and it is not disclosed that it has the performance of selective capacitive adsorption to remove heavy metal ions. Summary of the invention

[0006] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing a WS2 pseudocapacitor interface material.

[0007] Another object of the present invention is to provide a WS2 pseudocapacitor interface material prepared by the above method.

[0008] Another object of the present invention is to provide an application of the above-mentioned WS2 pseudocapacitive interface material in capacitive adsorption and removal of heavy metal ions.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a WS2 pseudocapacitor interface material comprises the following steps:

[0011] Sodium tungstate, thiourea, hydroxylamine hydrochloride and a surfactant are uniformly dispersed in deionized water to obtain a mixed solution; the mixed solution is heated to 160-200° C. for hydrothermal reaction, and the reaction product is separated, washed and dried to obtain a WS2 pseudocapacitor interface material.

[0012] Furthermore, the molar ratio of the sodium tungstate, thiourea and hydroxylamine hydrochloride is 0.5-0.6:2:1.

[0013] Furthermore, the amount of deionized water added is 5 to 10 times the total mass of sodium tungstate, thiourea and hydroxylamine hydrochloride.

[0014] Furthermore, the surfactant is CTAB (cetyltrimethylammonium bromide), and the added amount of CTAB is 0.5% to 2% of the mass of the mixed solution.

[0015] The present invention can improve the morphology and dispersed particle size of the WS2 pseudocapacitive interface material generated in the hydrothermal reaction process by adding the cationic surfactant CTAB, increase its specific surface area, and enhance the adsorption performance; on the other hand, more soft Lewis base sites S can be formed through the interaction between anions and cations. 2- The groups are exposed on the surface, and the above two effects significantly improve the capacitive adsorption and removal performance of the obtained WS2 pseudocapacitive interface material for heavy metal ions.

[0016] Furthermore, the pH value is adjusted to 5-7 before the hydrothermal reaction.

[0017] Furthermore, the hydrothermal reaction time is 12 to 48 hours.

[0018] Furthermore, the separation refers to filtering and separating the solid phase product; the washing refers to washing with deionized water and anhydrous ethanol; and the drying refers to drying at a temperature of 50 to 70° C. for 8 to 12 hours.

[0019] The above preparation method involves the following reaction:

[0020] Na2WO4+4CH4N2S+4H2O——4CO2+Na2WS4+8NH3,

[0021] Na2WS4+2NH2OH·HCl——WS2+N2+2H2O+2H2S+2NaCl.

[0022] A WS2 pseudocapacitor interface material is prepared by the above method.

[0023] The above-mentioned WS2 pseudocapacitive interface material is used in the capacitive adsorption to remove heavy metal ions. The application method is: using the WS2 pseudocapacitive interface material as the negative electrode of the capacitive deionization device and the activated carbon material as the positive electrode, and then removing the heavy metal ions by capacitive adsorption.

[0024] Furthermore, the voltage adsorbed by the capacitor is 0.1 to 5 V; and the heavy metal ions include at least one of Cr, Cd, Pb, Ni, Co, and Cu heavy metal ions.

[0025] The principle of the invention is that WS2 is a lamellar hollow sphere with a hexagonal crystal system, which has a unique SWS layered structure that can promote the insertion of ions into the interlayer space. In the WS2 layered structure, two layers of sulfur atoms are sandwiched between metal atoms, making more soft Lewis base sites S 2- The group is exposed on the surface. 2- The soft Lewis base sites have a high affinity for soft Lewis acid heavy metal ions. In addition, the central W atom of WS2 exhibits good pseudocapacitive properties due to its rich oxidation states (from +2 to +6), and can therefore be used for capacitive adsorption and removal of heavy metal ions.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention adopts sodium tungstate, thiourea and hydroxylamine hydrochloride to obtain WS2 pseudocapacitor interface material by hydrothermal reaction. The material has binding sites with affinity for heavy metal ions and exhibits good pseudocapacitor performance. The obtained WS2 pseudocapacitor interface material has a high affinity for Cr at a voltage of 1.2 V. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal rate of heavy metal ions can reach over 90%.

[0028] (2) The preparation method of the WS2 pseudocapacitive interface material of the present invention is simple, the reaction conditions are mild, and the cost is low; by adding a specific surfactant, the product morphology and active sites can be improved, thereby improving the capacitive adsorption and removal efficiency of heavy metal ions.

[0029] (3) Compared with conventional adsorption, chemical precipitation, ion exchange and membrane separation methods, the application method of the present invention in heavy metal removal has the advantages of high energy efficiency, environmental friendliness and no pollution, and has better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the WS2 pseudocapacitor interface material prepared in Example 1;

[0031] Figure 2 This is a diagram showing the removal efficiency of heavy metal ions by the WS2 pseudocapacitive interface material prepared in Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0033] Example 1

[0034] A method for preparing a WS2 pseudocapacitor interface material, the specific preparation steps are as follows:

[0035] 1.6493g sodium tungstate, 1.5224g thiourea, 0.6949g hydroxylamine hydrochloride and 0.24g surfactant CTAB were weighed and dispersed into 30mL deionized water, and the pH was adjusted to 6.0 by dropping 2mol / L hydrochloric acid or ammonia water under magnetic stirring to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180°C in a digital constant temperature oven for 24h. The obtained solid phase product was separated by suction filtration, washed with deionized water and anhydrous ethanol several times, and then placed in an oven at 60°C for 10h to obtain the WS2 pseudocapacitor interface material.

[0036] The scanning electron microscope image of the WS2 pseudocapacitor interface material obtained in this embodiment is as follows: Figure 1 It can be seen that the WS2 pseudocapacitive interface material obtained by the present invention is composed of blocks with a particle size of less than 10 μm.

[0037] The application of the WS2 pseudocapacitive interface material obtained in this embodiment in heavy metal removal is as follows:

[0038] The obtained WS2 / graphene electrode material was used as the negative electrode of the capacitive deionization device, and the activated carbon was used as the positive electrode of the capacitive deionization device. The capacitive adsorption of heavy metal solutions (containing Cr, Cr2+, Cr3+, Cr4+, ​​Cr6+, Cr7+, Cr8+, Cr8+, Cr9+, Cr10+, Cr11+, Cr12+, Cr13+, Cr14+, Cr15+, Cr16+, Cr17+, Cr18+, Cr19+, Cr22+, Cr19+, Cr18+, Cr19+, Cr1 ... 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ ) in the heavy metal ions. The solution adsorbed by the capacitor was tested by ICP-OES. The test results are as follows Figure 2 shown.

[0039] Depend on Figure 2 The results show that the WS2 pseudocapacitive interface material obtained in this embodiment has a high conductivity for Cr with a solubility of 10 ppm. 3+ 、Cd 2+ , Pb 2 + 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 94.45%, 94.92%, 90.98%, 93.67%, 89.69% and 93.61% respectively, and the solubility of Cr was 30ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 92.72%, 84.48%, 88.22%, 87.91%, 89.31% and 92.85% respectively, and the solubility of Cr was 50ppm. 3+ 、Cd 2+ , Pb 2 + 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 85.52%, 78.64%, 82.60%, 79.45%, 87.57% and 92.26% respectively, and the solubility of Cr was 70ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 84.20%, 67.38%, 75.67%, 74.74%, 72.61% and 86.71% respectively, and the solubility of Cr was 90ppm. 3+ 、Cd 2+ , Pb 2 + 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 82.79%, 59.76%, 71.53%, 71.89%, 69.08% and 72.10% respectively.

[0040] Example 2

[0041] A method for preparing a WS2 pseudocapacitor interface material, the specific preparation steps are as follows:

[0042] 1.6493g sodium tungstate, 1.5224g thiourea, 0.6949g hydroxylamine hydrochloride and 0.17g surfactant CTAB were weighed and dispersed into 30mL deionized water, and the pH was adjusted to 6.0 by dropping 2mol / L hydrochloric acid or ammonia water under magnetic stirring to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C in a digital constant temperature oven for 48h. The obtained solid phase product was separated by suction filtration, washed with deionized water and anhydrous ethanol several times, and then placed in an oven at 60°C for 10h to obtain the WS2 pseudocapacitor interface material.

[0043] The WS2 pseudocapacitive interface material obtained in this example is used as the negative electrode of the capacitor deionization device, and the activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the Cr with a solubility of 10ppm is3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions is 92.51%, 93.47%, 91.02%, 92.37%, 90.48% and 93.17% respectively. The solubility of Cr is 30ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 90.65%, 84.27%, 87.94%, 88.21%, 88.39% and 89.85% respectively, and the solubility of Cr was 50ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 84.76%, 79.80%, 81.54%, 80.23%, 85.69% and 90.71% respectively, and the solubility of Cr was 70ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 81.58%, 68.92%, 74.83%, 76.70%, 74.55% and 79.97% respectively, and the solubility of Cr was 90ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 79.07%, 62.74%, 69.81%, 70.43%, 66.59% and 69.76% respectively.

[0044] Example 3

[0045] A method for preparing a WS2 pseudocapacitor interface material, the specific preparation steps are as follows:

[0046] 1.6493g sodium tungstate, 1.5224g thiourea, 0.6949g hydroxylamine hydrochloride and 0.68g surfactant CTAB were weighed and dispersed into 30mL deionized water, and the pH was adjusted to 6.0 by dropping 2mol / L hydrochloric acid or ammonia water under magnetic stirring to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 200°C in a digital constant temperature oven for 12h. The obtained solid phase product was separated by suction filtration, washed with deionized water and anhydrous ethanol several times, and then placed in an oven at 60°C for 10h to obtain the WS2 pseudocapacitor interface material.

[0047] The WS2 pseudocapacitive interface material obtained in this example is used as the negative electrode of the capacitor deionization device, and the activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the Cr with a solubility of 10ppm is 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 94.45%, 94.92%, 90.98%, 93.67%, 89.69% and 93.61% respectively, and the solubility of Cr was 30ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 93.89%, 87.57%, 89.17%, 89.16%, 89.29% and 90.68% respectively, and the solubility of Cr was 50ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 88.64%, 80.72%, 81.65%, 80.22%, 88.31% and 89.63% respectively, and the solubility of Cr was 70ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 85.91%, 75.42%, 76.79%, 72.82%, 74.10% and 80.25% respectively, and the solubility of Cr was 90ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co2+ , Cu 2+ The removal efficiencies of heavy metal ions were 80.63%, 68.72%, 74.11%, 76.29%, 68.90% and 69.23% respectively.

[0048] Comparative Example 1

[0049] A method for preparing a WS2 pseudocapacitive interface material, compared with Example 1, does not add surfactant CTAB, and other conditions are the same.

[0050] The WS2 pseudocapacitive interface material obtained in this comparative example is used as the negative electrode of the capacitor deionization device, and the activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the Cr with a solubility of 10ppm is 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 41.20%, 52.65%, 73.77%, 72.00%, 61.40%, and 76.44%, respectively, for Cr with a solubility of 30 ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 26.37%, 49.00%, 64.50%, 65.21%, 45.32% and 70.73% respectively. The solubility of Cr was 50ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 8.23%, 17.17%, 29.48%, 59.06%, 23.46%, and 45.44%, respectively. The Cr concentration was 70 ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions is 5.63%, 9.68%, 26.35%, 27.72%, 10.69% and 32.53% respectively. The solubility of Cr is 90ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+The removal efficiencies of heavy metal ions were 5.26%, 5.15%, 12.66%, 19.85%, 9.38% and 31.53% respectively.

[0051] Comparative Example 2

[0052] A method for preparing a WS2 pseudocapacitive interface material, compared with Example 1, uses an equal amount of non-ionic surfactant AEO-10 ​​to replace CTAB, and other conditions are the same.

[0053] The WS2 pseudocapacitive interface material obtained in this comparative example is used as the negative electrode of the capacitor deionization device, and the activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the Cr with a solubility of 10ppm is 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 53.23%, 60.88%, 84.37%, 74.47%, 79.13% and 93.49% respectively. The solubility of Cr was 30ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 42.48%, 59.26%, 74.13%, 74.97%, 68.14% and 90.81% respectively, and the solubility of Cr was 50ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiency of heavy metal ions was 23.89%, 43.10%, 53.35%, 70.99%, 48.04% and 85.44% respectively. The solubility of Cr was 70ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+ The removal efficiencies of heavy metal ions were 11.03%, 19.43%, 39.21%, 35.85%, 27.77% and 73.33% respectively, and the solubility of Cr was 90ppm. 3+ 、Cd 2+ , Pb 2+ 、Ni 2+ 、Co 2+ , Cu 2+The removal efficiencies of heavy metal ions were 10.37%, 17.20%, 32.56%, 29.66%, 17.20% and 40.66%, respectively.

[0054] By comparing the results of Comparative Examples 1 to 2 with Example 1, it can be seen that when no surfactant is added during the hydrothermal reaction or a nonionic surfactant is used to replace CTAB, the capacitive adsorption and removal efficiency of heavy metal ions by the obtained WS2 pseudocapacitive interface material is significantly reduced. The reason is that the addition of surfactant can improve the morphology and dispersed particle size of the WS2 pseudocapacitive interface material generated during the hydrothermal reaction, increase its specific surface area, and enhance the adsorption performance; and the use of the specific cationic surfactant CTAB of the present invention can also make more soft Lewis base sites S through the interaction between anions and cations. 2- The groups are exposed on the surface, which increases the affinity for soft Lewis acid heavy metal ions, thereby further significantly improving the capacitive adsorption and removal performance of heavy metal ions.

[0055] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a WS2 pseudocapacitive interface material, characterized in that: The method comprises the following preparation steps: Sodium tungstate, thiourea, hydroxylamine hydrochloride and a surfactant are uniformly dispersed in deionized water to obtain a mixed solution; the mixed solution is heated to 160-200° C. for hydrothermal reaction, and the reaction product is separated, washed and dried to obtain a WS2 pseudocapacitor interface material.

2. The method for preparing a WS2 pseudocapacitive interface material according to claim 1, characterized in that: The molar ratio of the sodium tungstate, thiourea and hydroxylamine hydrochloride is 0.5-0.6:2:

1.

3. The method for preparing a WS2 pseudocapacitive interface material according to claim 1, characterized in that: The amount of deionized water added is 5 to 10 times the total mass of sodium tungstate, thiourea and hydroxylamine hydrochloride.

4. The method for preparing a WS2 pseudocapacitive interface material according to claim 1, characterized in that: The surfactant is CTAB, and the added amount of CTAB is 0.5% to 2% of the mass of the mixed solution.

5. The method for preparing a WS2 pseudocapacitive interface material according to claim 1, characterized in that: The pH value is adjusted to 5-7 before the hydrothermal reaction.

6. The method for preparing a WS2 pseudocapacitive interface material according to claim 1, characterized in that: The hydrothermal reaction time is 12 to 48 hours.

7. The method for preparing a WS2 pseudocapacitive interface material according to claim 1, characterized in that: The separation refers to filtering and separating the solid phase product; the washing refers to washing with deionized water and anhydrous ethanol; and the drying refers to drying at a temperature of 50 to 70° C. for 8 to 12 hours.

8. A WS2 pseudocapacitive interface material, characterized in that: It is prepared by the method according to any one of claims 1 to 7.

9. The use of a WS2 pseudocapacitive interface material as claimed in claim 8 in capacitive adsorption to remove heavy metal ions, characterized in that: The application method is: using the WS2 pseudocapacitive interface material as the negative electrode of a capacitive deionization device, using the activated carbon material as the positive electrode, and then removing heavy metal ions through capacitive adsorption.

10. The use of a WS2 pseudocapacitive interface material according to claim 9 in capacitive adsorption to remove heavy metal ions, characterized in that: The voltage adsorbed by the capacitor is 0.1-5V; the heavy metal ions include at least one of Cr, Cd, Pb, Ni, Co, and Cu heavy metal ions.

Citation Information

Patent Citations

  • Preparation method of GO / MoS2 electrode for removing lead ions in water by electrochemical method

    CN111302445A

  • Preparation and application of tungsten disulfide / indium sulfide heterojunction photocatalytic material

    CN113385195A

  • Ferrous disulfide / tungsten disulfide composite catalyst as well as preparation method and application thereof

    CN115041197A

  • Molybdenum selenide / mesoporous hollow carbon sphere composite electrode material and preparation method and application thereof

    CN115636475A

  • Carbon-coated tungsten oxide composite electrode material and preparation method and application thereof

    CN115636480A